Sex differences in clinical characteristics and outcomes after myocardial infarction: insights from the Valsartan in Acute Myocardial Infarction Trial (VALIANT). (6th February 2015) - Lam, Carolyn S. P.; McEntegart, Margaret; Claggett, Brian; Liu, Jiankang; Skali, Hicham; Lewis, Eldrin; Køber, Lars; Rouleau, Jean; Velazquez, Eric; Califf, Rob; McMurray, John J.; Pfeffer, Marc; et al.
<x xml:space="preserve">Abstract</x> Background We examined the association of sex with clinical characteristics and outcomes in patients following myocardial infarction (MI) in the Valsartan in Acute Myocardial Infarction Trial (VALIANT). Methods and Results A total of 4570 women and 10 133 men with heart failure (HF), left ventricular systolic dysfunction or both were enrolled 0.5–10 days after myocardial infarction (MI) and followed for a median of 24.7 months. Compared with men, women were older, had more comorbidities, and were more likely to present in Killip Class III/IV and experience post‐infarction angina or HF. After adjusting for baseline differences, both short‐term and longer‐term mortality were similar in men and women. However, women were more likely than men to experience the composite outcome of cardiovascular death, MI, HF, stroke, and resuscitation from cardiac arrest [adjusted hazard ratio (HR) 1.15; 95% confidence interval (CI); 1.06–1.24, P = 0.001], mainly owing to an increased risk of hospitalization for HF (adjusted HR 1.36; 95% CI 1.22–1.52; P < 0.001). In a subset of patients who underwent echocardiographic study (n = 603), women had smaller left ventricular volumes indexed by body size than men but similar ejection fractions and similar changes in ventricular volumes from baseline to 1 month and 20 months. Conclusions In VALIANT, the risk of HF following MI was higher in women than men after adjusting for age and comorbidities, although the risk of other fatal and non‐fatal outcomes were similar. The higher long‐term risk of HF in women appears to be independent of the extent of left ventricular systolic dysfunction or remodelling compared with men.